Depth differentiation of microbial communities and nutrient cycling functional genes in semi-arid riparian soil - Liu, Yutong; Wang, Jinxuan; Wei, Wei; Xia, Manhong; Ji, Deshuai; Wang, Fan; Zhang, Xuanming; Wang, Wenke (Frontiers in Microbiology, 2025)
IntroductionMicrobial communities and their associated carbon, nitrogen, and phosphorus metabolic processes play a role in maintaining ecological functions and nutrient cycling in riparian zones. However, systematic research on the coupling mechanisms of carbon, nitrogen, and phosphorus biogeochemical processes in soil profiles of semi-arid riparian soil is still limited.MethodsThis study focused on the riparian zone of the Tuwei River, a typical semi-arid river. Metagenomic sequencing was used to analyze the composition of microbial communities and their carbon, nitrogen, and phosphorus metabolic functions across different soil depths along the river.ResultsThe dominant taxa across all depths and river sections were Proteobacteria (average relative abundance 49.85%) and Serratia (11.23%). Results from ANOVA and Tukey–Kramer post-hoc multiple comparison tests showed that microbial diversity significantly decreased with increasing soil depth (p < 0.05). Gene families associated with carbon fixation (accC, pccB), denitrification (nosZ, nirK), and phosphorus metabolism (purC, guaB, pyrG) were significantly enriched in surface soils and showed clear depth-dependent declines (p < 0.05). Partial Mantel tests revealed that microbial metabolic functions were significantly correlated with porosity (p < 0.05), soil organic carbon, total nitrogen, and total phosphorus, confirming that nutrient availability and soil structure are key regulators of microbial biogeochemical functions.ConclusionOur findings reveal that nutrient availability and soil structure jointly regulate the vertical distribution of microbial metabolic functions. These insights provide a scientific basis for ecological restoration and soil management in semi-arid riparian zones, where optimizing surface structure and nutrient inputs can stimulate microbial-driven biogeochemical cycling. Key functional taxa and genes may also serve as sensitive indicators for evaluating restoration effectiveness under climate-induced stress.